2022
DOI: 10.1109/access.2022.3215154
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Art of Information Integration in Space Applications

Abstract: This paper aims to present a comprehensive survey on information integration (II) in space informatics. With an ever-increasing scale and dynamics of complex space systems, II has become essential in dealing with the complexity, changes, dynamics, and uncertainties of space systems. The applications of space II (SII) require addressing some distinctive functional requirements (FRs) of heterogeneity, networking, communication, security, latency, and resilience; while limited works are available to examine recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 201 publications
0
3
0
Order By: Relevance
“…A wide scope of the responses to this SS from so many scholars in multiple disciplines has confirmed that advancing SII is challenging but crucial to meet some unique requirements of complex space systems in terms of latency, heterogeneity, communication, networking, security, and resilience; many research problems remain unsolved, newly developed information technologies should be widely explored in SII for sensing, communication, networking, data mining, and decision-making supports of complex space information systems [4]. The editorial team would also…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A wide scope of the responses to this SS from so many scholars in multiple disciplines has confirmed that advancing SII is challenging but crucial to meet some unique requirements of complex space systems in terms of latency, heterogeneity, communication, networking, security, and resilience; many research problems remain unsolved, newly developed information technologies should be widely explored in SII for sensing, communication, networking, data mining, and decision-making supports of complex space information systems [4]. The editorial team would also…”
Section: Discussionmentioning
confidence: 98%
“…The accepted articles in this SS have shown a high diversity in research topics, methodologies, and objectives. Their main contributions are summarized in four categories as follows [4].…”
mentioning
confidence: 99%
“…A space product does not appear in any binding act of law. Rather it is a concept that is being discussed in works regarding space-based economy (Engelbert & Harper, 2022;In-Space, 2022 ), materials and life science in outer space (Seoane-Viaño et al, 2022), orbital manufacturing (Bi et al, 2022) and patent law (Burk, 1991). Its relations to space law are minuscule, as manufacturing of a space product falls under national provisions for authorization and supervision under article VI of the OST -as they mostly do not affect any other space object besides their manufacturing space factory (Abeyta, 2017).…”
Section: Space Productsmentioning
confidence: 99%